The SWOT Analysis of Chicken Eggs Marketing Strategy in Konda District South Konawe Regency During the Covid-19 Pandemic - Al Yasir, Muhammad Fiqram; Bahari, Bahari; Zani, Munirwan (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2022)
This study aims to determine internal factors, external factors and alternative marketing strategies during the Covid-19 pandemic. This research was carried out in Lalowiu Village, Konda District, South Konawe Regency, from August 2021 to April 2022. The object of this research is Livestock Core Business using the case study method. The research analysis used quantitative descriptive analysis and SWOT analysis. The data used in this study are primary data and secondary data. The data collection technique used was interviews and recording. The results showed that the Livestock Core Business internals included transportation equipment, affordable egg prices, sources of capital, and location far from the market. And the external factors of the Livestock Core Business include; having retail customers in several places, being readily accepted in the market, many competitors, expensive feed resources, and road access. The strategy to market broiler eggs, namely the SO strategy, consists of increasing production and expanding and maintaining the existing market. ST strategy consists of increasing product quality and quantity and improving packaging. The WO strategy consists of adding human resources. The WT strategy includes adding partners in nearby cities and making organic feeds.